The Bloomsbury Handbook to Agatha Christie - Evans, Mary Anna; Bernthal, J.C. (New York, USA : Bloomsbury Academic, 2022)
"The first specifically academic companion to contemporary scholarship on the work of Agatha Christie, this book includes chapters by an international group of scholars writing on topics and fields of study as various as ecocriticism and the anthropocene, popular modernism, middlebrow fiction, queer theory, feminism, crime and the state, and more. It addresses a broad selection of Christie's crime novels, as well as her short stories, literary novels written pseudonymously, and her own and others' dramatic adaptations for television, film, and the stage, Featuring unprecedented access to images and content held in Christie's personal archive, as well as a Foreword from renowned crime fiction writer Val McDermid, this is essential reading for anyone interested in Christie's work and legacy"--
Keywords: English Literature; Handbook